2020
DOI: 10.3390/app10176137
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Monitoring under Transient Conditions: A New Paradigm in Electric Motors Predictive Maintenance

Abstract: Electric motors condition monitoring is a field of paramount importance for industry. In recent decades, there has been a continuous effort to investigate new techniques and methods that are able to determine the health of these machines with high accuracy and reliability. Classical methods based on the analysis of diverse machine quantities under stationary conditions are being replaced by modern methodologies that are adapted to any operation regime of the machine (including transients). These new methods (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Steady-state analysis employs FEM to model the machine in greater detail. Focus has shifted into flux analysis, due to sensory advancements and its richer harmonic content [4]. Cutting edge approaches investigate AI and Fuzzy Cognitive Maps (FCM) decision making to distinguish fault indications.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Steady-state analysis employs FEM to model the machine in greater detail. Focus has shifted into flux analysis, due to sensory advancements and its richer harmonic content [4]. Cutting edge approaches investigate AI and Fuzzy Cognitive Maps (FCM) decision making to distinguish fault indications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Great reviews, such as [1][2][3][4][5][6], concerning state-of-the-art PM methods and their application have been published in recent years, addressing techniques with their applications and comparison. Literature highlights a need for evaluation benchmarks and new combinations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some fault diagnosis techniques benefit from signals of the machine obtained naturally during start‐up and switch‐off transients. It has been demonstrated that fault signatures are more detectable in these cases, and their dynamic behaviour reveals useful information for distinguishing different types of faults and also, phenomena causing false alarms such as rotor core magnetic anisotropy [3, 79].…”
Section: Magnetic Flux‐based Fault Signaturesmentioning
confidence: 99%
“…Various types of quantities, including mechanical vibration, temperature, noise, electrical current, and voltage, have been studied for this purpose. Nonetheless, after many years now, the consensus is that there is no method based on a single quantity that can provide a comprehensive knowledge of the machine's health conditions [3]. Most commercialised techniques are based on motor current signature analysis (MCSA), which has been proved to be susceptible to false/missed alarms.…”
Section: Introductionmentioning
confidence: 99%
“…Space vector angular fluctuation is a method where the difference between the space vector angle and the angle of an ideal space vector is considered in the frequency domain [11]. A transient analysis that has become widely used in recent years is ATCSA, which is based on time-frequency analysis of the motor current [12,13]. ATCSA has also been applied on VSD-driven motors for the diagnosis of different kinds of faults [4].…”
Section: Introductionmentioning
confidence: 99%